Public health implications of severe floods in Pakistan: assessing the devastating impact on health and the economy - Raza, Mahnoor; Fatima, Alina; Habiba, Ume; Shah, Hussain Haider (Frontiers in Environmental Science, 2023)
Natural disasters, including droughts, earthquakes, landslides, and floods, cause human mortality, property destruction, and social and economic turmoil. More than 33 million people in Pakistan have been impacted by floods due to the recent heavy rains. Many public hospitals, water treatment plants, and educational institutions have also been damaged or destroyed. Water and vector-borne diseases may have spread more widely due to the floods. A rapid health emergency response must be initiated to treat the injured, stocking healthcare facilities with vital supplies and back up mobile health teams in the impacted areas.